2019
DOI: 10.1145/3282438
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Choice of When to Garbage Collect

Abstract: We consider the ultimate limits of program-specific garbage collector (GC) performance for real programs. We first characterize the GC schedule optimization problem. Based on this characterization, we develop a linear-time dynamic programming solution that, given a program run and heap size, computes an optimal schedule of collections for a non-generational collector. Using an analysis of a heap object graph of the program, we compute a property of heap objects that we call their pre-birth time. This informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Prior work by Jacek et al gave a dynamic programming algorithm to compute the optimal GC locations (in terms of reducing GC execution time) given an execution trace of a program on a particular input [12]. Later, Jacek et al showed that supervised learning techniques could be used to generalize these execution traces to other inputs [11].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work by Jacek et al gave a dynamic programming algorithm to compute the optimal GC locations (in terms of reducing GC execution time) given an execution trace of a program on a particular input [12]. Later, Jacek et al showed that supervised learning techniques could be used to generalize these execution traces to other inputs [11].…”
Section: Related Workmentioning
confidence: 99%
“…For some programs, the location where GC is performed can impact performance [12]. For example, if a function creates many allocations that will soon have their reference count reach zero (triggering an automatic collection), garbage collection may waste time scanning these allocations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation